Empirical Study: Electricity Consumption as a Driver of Economic Growth in Maritime Communities - Nur Effendi Anwar; Mursal Mursal; Andi Mulyadi; Raymond Raymond (Studi Ekonomi dan Kebijakan Publik, 2026)
Purpose: Economic growth in coastal and maritime areas is significantly influenced by electricity availability, efficiency, and sustainability. This study examines the amount of electricity used and its relationship with economic growth. in the maritime communities of the Batam City. Methodology/approach: This study uses a quantitative empirical approach based on secondary data from PLN Batam, BPS, and the Maritime Affairs and Fisheries Service for the 2015–2024 period. Multiple linear regression and Granger causality tests were used to examine the relationship between electricity consumption and Batam's maritime economic growth. Results/findings: Electricity consumption has a positive and significant impact on maritime economic growth; a 1% increase in electricity consumption increases GDP by 0.63%, with a two-way causal relationship between electricity and the economic growth of coastal communities. Conclusions: Electricity consumption has been shown to be strongly and significantly related to Batam City's maritime economic growth, particularly in the industrial and fisheries sectors. The increasing electricity demand in line with economic growth until 2030 has the potential to put pressure on the electricity system, making energy efficiency a key strategy to ensure sustainable economic growth, energy security, and environmental impact management. Limitations: These findings emphasize the importance of reliable, efficient, and affordable electricity supply policies for supporting maritime-based economic development in Batam. Contributions: The study also recommends building renewable energy systems, such as solar power plants along the coast, as a good long-term plan to help support the blue economy sustainably. and the energy security of maritime communities.